A Holistic Perspective on Corporate Sustainability Drivers. (3rd April 2013) - Lozano, Rodrigo
Abstract Since company boards are increasingly discussing 'sustainability', it becomes necessary to examine the nature of sustainability drivers. Most approaches to corporate sustainability drivers have focused either on internal or external drivers. This paper is aimed at providing a more holistic perspective on the different corporate sustainability drivers in order to better catalyse change from the unsustainable status quo to a more sustainable‐oriented state. Empirical data was collected from experts and company leaders. The findings show that, internally, leadership and the business case are the most important drivers, whilst the most important external drivers are reputation, customer demands and expectations, and regulation and legislation. The paper proposes a corporate sustainability driver model, which considers both internal and external drivers, and complements these with drivers that connect them. This offers a holistic perspective on how companies can be more proactive in their journey to becoming more sustainability orientated. Copyright © 2013 John Wiley & Sons, Ltd and ERP Environment